2021
DOI: 10.1177/02637758211036467
|View full text |Cite
|
Sign up to set email alerts
|

Dispossession as depotentiation

Abstract: This paper proposes a theory of urban dispossession as depotentiation. ‘Depotentiation’, as I employ the term, indicates the diminishment of imminent capacities, affects and potentialities. I propose this formulation to both complement and critique Harvey’s dominant notion of accumulation by dispossession as the commodification of the urban commons and to contribute to conceptual developments on the stratified and affective dimensions of eviction. The evictions in my study operate in liminal urban spaces where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(35 reference statements)
1
12
0
2
Order By: Relevance
“…As contemporary studies on kampung resistance and collaborative kampung revitalization have shown, the outcomes of kampung eviction do not always follow a tidy trajectory since some managed to keep on 'dwelling in liminalities' or even produce new hybrids modes of living (Lancione and Simone, 2021 : 970). Nevertheless, we join a chorus of recent studies that are cognizant of the limitations of resistance (Wilhelm-Solomon, 2021 ;Maqsood and Sajjad, 2021 ). As Baker ( 2021 : 808) contends, eviction is the way the state appropriates time and space through 'linked materials, people, and technologies across the multiple axes'.…”
Section: Discussionmentioning
confidence: 99%
“…As contemporary studies on kampung resistance and collaborative kampung revitalization have shown, the outcomes of kampung eviction do not always follow a tidy trajectory since some managed to keep on 'dwelling in liminalities' or even produce new hybrids modes of living (Lancione and Simone, 2021 : 970). Nevertheless, we join a chorus of recent studies that are cognizant of the limitations of resistance (Wilhelm-Solomon, 2021 ;Maqsood and Sajjad, 2021 ). As Baker ( 2021 : 808) contends, eviction is the way the state appropriates time and space through 'linked materials, people, and technologies across the multiple axes'.…”
Section: Discussionmentioning
confidence: 99%
“…Davidson (2009), Davidson and Lees (2005), and Marcuse (1985) were particularly influential in loosening the grip of Cartesian understandings of space on critical gentrification studies, and their work has ushered in a wide range of research that takes seriously the experiential, emotional, and otherwise more-than-material dimensions of displacement. For example, geographers have shown via case studies of gentrification in places like the Brooklyn neighborhoods of Greenpoint (Stabrowski, 2014) and Bushwick (Valli, 2015), the London borough of Hackney (Butcher and Dickens, 2016), Mexico City (Linz, 2021), and elsewhere, that in addition to processes of spatial dislocation for ethnic minorities, the elderly, and working-class residents, gentrification occurs in psychic (Fullilove, 1996; Ji, 2021; Meyer, 2021; Seitz, 2022; Westin, 2021) and affective registers (Addie and Fraser, 2019; Frank, 2021; Jones and Evans, 2012; Linz, 2017; Pain, 2019; Wilhelm-Solomon, 2021) through the everyday loss of “agency, freedom, and security to ‘make place’” (Stabrowski, 2014: 795). Throughout this work we find recognition that in many instances of gentrification, “it is the relationship to a place that is displaced, rather than an individual being physically removed” (Wynne and Rogers, 2021: 397).…”
Section: Engaging Affect In the Study Of Displacement-by-gentrificationmentioning
confidence: 99%
“…This is the dimension of displacement beyond dislocation or rupture—displacement as the production of new affective relations in and with place. To be clear, we are not critiquing the crucial focus in this scholarship on how displacement functions, in the words of Wilhelm-Solomon (2021: 977), as “depotentiation”—“the diminishment of both power and [affective] potentiality” (see also McElroy and Werth, 2019). But we are emphasizing that dislocation, depotentiation, etc., are always partial descriptions of the displacement process.…”
Section: Engaging Affect In the Study Of Displacement-by-gentrificationmentioning
confidence: 99%
“…Like homing (Boccagni, 2022), unhoming recognizes the dynamic and varied nature of home and the ways in which wider structural forces can be fundamental to the unmaking of home (Baxter and Brickell, 2014). In this article we reflect on the unmaking of home in different ways, attending to the 'personal and political, inside and outside, private and public' (Handel, 2019(Handel, : 1051, the 'lived and felt realities of housing insecurity' (Vasudevan, 2022(Vasudevan, : 1539 and the displacement of affective capabilities (Wilhelm-Soloman, 2021).…”
Section: Unhoming and Urban Traumamentioning
confidence: 99%
“…Although waiting may appear to be a passive modality, there are also 'many cases where agency oozes out of waiting' (Hage, 2009a: 1). Inhabiting marginality and dispossession can therefore be a productive space, with opportunities for building solidarity (Maqsood and Sajjad, 2021), albeit with differential potentialities for mobilization (Wilhelm-Soloman, 2021). The building safety crisis has generated a new politics of waiting, offering potential to attend to 'the rich plurality of the social forms that waiting takes … and the social and political relations that shape and flow from it' (Hage, 2009a: 2).…”
Section: Modalities Of Waitingmentioning
confidence: 99%